EndoC-βH5 cells are storable and ready-to-use human pancreatic beta cells with physiological insulin secretion - Bruno Blanchi; Marion Taurand; Claire Colace; Sofia Thomaidou; Charlotte Audeoud; Federica Fantuzzi; Toshiaki Sawatani; Sevda Gheibi; Joan Sabadell-Basallote; Fransje W.J. Boot; Thibault Chantier; Aline Piet; et al. (Elsevier, 2023)
Objectives: Readily accessible human pancreatic beta cells that are functionally close to primary adult beta cells are a crucial model to better understand human beta cell physiology and develop new treatments for diabetes. We here report the characterization of EndoC-βH5 cells, the latest in the EndoC-βH cell family. Methods: EndoC-βH5 cells were generated by integrative gene transfer of immortalizing transgenes hTERT and SV40 large T along with Herpes Simplex Virus-1 thymidine kinase into human fetal pancreas. Immortalizing transgenes were removed after amplification using CRE activation and remaining non-excized cells eliminated using ganciclovir. Resulting cells were distributed as ready to use EndoC-βH5 cells. We performed transcriptome, immunological and extensive functional assays. Results: Ready to use EndoC-βH5 cells display highly efficient glucose dependent insulin secretion. A robust 10-fold insulin secretion index was observed and reproduced in four independent laboratories across Europe. EndoC-βH5 cells secrete insulin in a dynamic manner in response to glucose and secretion is further potentiated by GIP and GLP-1 analogs. RNA-seq confirmed abundant expression of beta cell transcription factors and functional markers, including incretin receptors. Cytokines induce a gene expression signature of inflammatory pathways and antigen processing and presentation. Finally, modified HLA-A2 expressing EndoC-βH5 cells elicit specific A2-alloreactive CD8 T cell activation. Conclusions: EndoC-βH5 cells represent a unique storable and ready to use human pancreatic beta cell model with highly robust and reproducible features. Such cells are thus relevant for the study of beta cell function, screening and validation of new drugs, and development of disease models.